Physical and chemical foundations of the technology for obtaining uranium oxides - Mukhachev, A.P.; Yelatontsev, D.O.; Kharitonova, O.A. (Вопросы атомной науки и техники, 2022)
The article presents the results of industrial testing of processes for obtaining high-purity uranium compounds, including extraction, concentration, and purification of uranium from a mixture of nitric and phosphoric acids, solid-phase stripping, and reduction of U(VI) to U(IV). It is shown that the combination of three different extraction lines for the concentration and purification of uranium from accompanying valuable elements and radioactive isotopes makes it possible to obtain a natural uranium concentrate with a low content of impurities, which determine the economics of uranium hexafluoride production. The processes of drying and roasting of crystals of ammonium uranyl tricarbonate after solid-phase re-extraction in an atmosphere of reducing gases of ammonia and hydrogen make it possible to obtain uranium dioxide suitable for fluorination to obtain tetra and uranium hexafluoride.